Effect of Addition of Sugarcane Bagasse Activated Charcoal (Saccharum officinarum L) on Reducing Peroxide Numbers in Cooking Oil - Farah Fajarna; Erva Reyhani; Safrida Kemala Putri (International Journal of Seocology, 2022)
A research has been conducted entitled "The Effect of Addition of Sugarcane Bagasse Activated Charcoal (Saccharum Officinarum L) on Reducing Peroxide Numbers in Cooking Oil". The basis of this research, cooking oil that is used repeatedly and undergoes an excessive heating process causes a decrease in the quality of cooking oil, which is indicated by an increase in the peroxide value of the oil. Improving the quality of cooking oil can be done by adding activated charcoal made from bagasse. This study aims to determine the effect of adding sugarcane bagasse activated charcoal to decrease the peroxide number. This research was carried out at the Chemical Laboratory of the Aceh Government Health Analyst Academy using the experimental method, the population in this study was cooking oil. After doing research using the Iodometry method, the results obtained for the addition of 1% bagasse activated charcoal to reduce the peroxide value by 3,597 meq O2/100 gr (40%), the addition of 2% bagasse activated charcoal resulted in a decrease of 1,417 meq O2/100 gr (76.36%), and the addition of 3% bagasse activated charcoal resulted in a decrease of 1.253 meq O2/100 gr (79.09%). Thus it can be concluded that the addition of bagasse activated charcoal can reduce the level of peroxide value in cooking oil.